Optimization of Financing Role of Islamic Banks Development of Micro Small and Medium Enterprises (MSME) In Bandar Lampung - A. Zuliyansyah (Journal of Islamic Business and Economic Review, 2019)
The development potential of MSME in Indonesia can not be separated from the support of banks in lending to MSMEs. MSME loans are loans to borrowers of micro, small and medium enterprises that meet the definition and criteria of micro, small and medium enterprises as stipulated in Law No. 20 of 2008 on MSMEs. Under the bill, MSMEs are productive businesses that meet the criteria of business within certain constraints net worth and annual sales revenue. This study aims to look at how is the implementation of Islamic bank financing for the development of MSMEs in the city of Bandar Lampung. Are the problems faced by Islamic banks in financing to MSMEs in Bandar Lampung and how efforts can be taken to optimize the Syariahagainst Bank financing the development of MSMEs in the city of Bandar Lampung. From the results of field research on MSMEs respondents conclusion that the financing of consumption used for productive activities can reach ± 40% of the total MSME financing consumption. The number is obtained by adding the percentage of the use of pure MSME consumer financing for business activities (28%), for personal purposes which turned out to be used for business activities (8.7%) and the use of financing for personal use and business activities or the use of "combined" (3%). Percentage of financing that is in a group of "combined" with the added consideration that MSMEs often do not separate the use of financing for private and business purposes. Banks tend to classify the proposed financing by MSMEs, especially small and micro financing, into financing consumption with the reason for easier consumer finance bank in the analysis of financing and banks are better off because of consumer financing interest rate is relatively higher than financing productive. Moreover, in terms of reporting, particularly in the economic sector, consumer finance easier clasification, because it will automatically go into the sector "others".Financing the development of Islamic banking in the development of MSMEsin Bandar Lampung during the years 2016-2017 has increased to fluctuate. This reflects that the role of Islamic banking and financing in the improvement of micro, small and medium enterprises (MSMEs) in the city of Bandar Lampung is not optimal.